The Role of Entrepreneurship Policy in College Students’ Entrepreneurial Intention: The Intermediary Role of Entrepreneurial Practice and Entrepreneurial Spirit - Huang, Yangjie; An, Lanyijie; Wang, Jing; Chen, Yingying; Wang, Shuzhang; Wang, Peng (Frontiers in Psychology, 2021)
Entrepreneurship is a sustainable development tool that supports the alleviation of poverty and unemployment. Focusing on the promotion of entrepreneurial intention (EI) under the background of entrepreneurship education (EE), this study used a structural equation model to examine the effect of entrepreneurship policy (EPo), entrepreneurial practice (EPr), and entrepreneurial spirit (ES) on the EI of 384 college students from 22 universities in Guangdong Province. The test results show that there are significant positive correlations between EPo and EI; EPo and EPr; EPo and ES; and EPr and EI. They also support the hypothesis that EPr enhances the positive effect that EPo has on EI. This study puts forth measures to improve EI and makes contributions to future research on EE.